2023
DOI: 10.1002/adom.202301001
|View full text |Cite
|
Sign up to set email alerts
|

B‐Site Doping of Metal Halide Perovskite Nanoplatelets Influences Their Optical Properties

Aleksandr P. Litvin,
Igor V. Margaryan,
Wenxu Yin
et al.

Abstract: Metal halide perovskite nanoplatelets (NPls) have recently joined a rich family of 2D semiconductor nanomaterials. Quantum and dielectric confinement in these nanostructures endow them with useful optical properties, which include, but are not limited to, high linear and nonlinear absorption coefficients, narrow and tunable emission bands, and high photoluminescence quantum yield. These characteristics render perovskite NPls promising for applications in lighting, photodetection, nonlinear optics, and photocat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 139 publications
0
4
0
Order By: Relevance
“…The basic idea is to reduce the numbers of defects and vacancies and to improve the lattice ordering of [PbX 6 ] 4− octahedra for enhanced PLQYs. [30][31][32][33] Recently, various dopants like transition metals (Mn 2+ , Ni 2+ , Cd 2+ , Co 2+ etc.) and alkaline Earth metals (Ba 2+ , Sr 2+ , Ca 2+ etc.)…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The basic idea is to reduce the numbers of defects and vacancies and to improve the lattice ordering of [PbX 6 ] 4− octahedra for enhanced PLQYs. [30][31][32][33] Recently, various dopants like transition metals (Mn 2+ , Ni 2+ , Cd 2+ , Co 2+ etc.) and alkaline Earth metals (Ba 2+ , Sr 2+ , Ca 2+ etc.)…”
Section: Introductionmentioning
confidence: 99%
“…have been incorporated into CsPbX 3 NCs. [32][33][34][35][36][37] It is generally observed that doping of perovskite NCs enhances their crystallinity, charge recombination efficiency and PL behaviour with improved PLQYs. Yong et al reported near-unity PLQYs of mixed halide CsPbCl x Br 3−x NCs (x = 1.5, 2.4, 3) by Ni 2+ doping.…”
Section: Introductionmentioning
confidence: 99%
“…Exceptional optical properties of lead halide perovskite nanocrystals (NCs) have positioned them as leading materials for applications in photonics, optoelectronics, and nonlinear optics. The inherent defect tolerance of perovskite NCs, coupled with the rapid development of their synthesis methods and surface passivation approaches, enables strong emission from perovskite NCs over the entire visible spectral range . Moreover, the soft ionic perovskite matrix serves as an ideal host for various self-emissive dopants. One of the most notable examples is the doping of perovskite NCs with Mn 2+ ions, resulting in orange emission arising from the parity-forbidden 4 T 1 → 6 A 1 d – d transition. Alternatively, doping perovskite nanostructures with emissive lanthanide ions opens up the possibility of tuning the emission band to the near-infrared (NIR) spectral range. Of particular interest is the doping of perovskite NCs with ytterbium (Yb 3+ ) ions emitting at ∼980 nm, leading to extremely high values of photoluminescence quantum yield (PL QY) in the NIR range, often exceeding 100%. , The exceptional efficiency of NIR emission in doped perovskite NCs further propels the development of these materials for utilization in light-harvesting and light-emitting applications. …”
mentioning
confidence: 99%
“…Quantum-confined perovskite nanoplatelets (Pe-NPLs) have emerged as another promising blue emitter due to their thickness-tunable emissions, narrow PL full-width at half-maximums (fwhm’s), and large exciton binding energies. , Among the family of Pe-NPLs, pure Br-based CsPbBr 3 NPLs with 3-monolayer thickness are desired to achieve pure-blue emissions (460–470 nm). , Nevertheless, their electroluminescence (EL) performance is challenged by the notorious red-shift of the emission for solid-state films and the poor electrical conductivity of surface-capped insulating bulky hydrocarbon chains which severely impede the charge carrier transfer into the NPL-emitting layer. , Although using a polymer (such as polyethylenimine) to cap the surface of CsPbBr 3 NPLs could prevent their transformation into bulk and thus improve the emission stability of solid-state films, the barriers for charge carriers to transfer between NPLs will get even higher. , Many efforts have been devoted to reducing either the density of surface ligands or their chain lengths to improve the charge transport capability of CsPbBr 3 NPLs without compromising their structure stability, which, however, usually suffers from reduced PL quantum yields (PLQYs) in solid-state films and thus makes it hard to achieve the desired efficient pure-blue EL performance.…”
mentioning
confidence: 99%